RECENT BRACHIOPODS FROM SOUTH ATLANTIC OCEAN: FIRST OCCURRENCE OF THE LINGULIDAE AND ITS BIOGEOGRAPHIC IMPLICATIONS: Braquiópodes recentes do oceano Atlântico Sul: primeira ocorrência de Lingulidae e suas implicações biogeográficas - Augusto Correia Monteiro, Felipe; Xerez Barroso, Cristiane; Franklin Junior, Wilson; Matthews-Cascon, Helena; C. Emig, Christian (Arquivos de Ciências do Mar, 2022)
The brachiopod fauna of the South Atlantic is significantly abundant and appears to be predominantly composed of cosmopolitan species. However, until now there was no record of inarticulate brachiopods of the Family Lingulidae in this region. The present study describes the first occurrence of lingulid brachiopods in the South Atlantic. Seven specimens were collected on the continental shelf of the Maranhão state, Northeastern Brazil, Western South Atlantic. The individuals were identified as belonging to the genus Lingula. Although brachiopods have great dispersion capability durintg their larval phase, the hypothesis that these specimens arrived on the Brazilian coast as a result of human activities cannot be ruled out. Keywords: Lingula, subfilo Linguliformea, “Inarticulata”, inarticulate brachiopods, Brazil.